Introdução de tópicos de Física Térmica e Cristalografia no ensino médio utilizando um simulador mecânico - Cristino, Wesley Moura Boracchi (2022)
In the last decades, physics education research has shed light on the difficulties and obstacles that students and teachers encounter in learning physics. In response, a wide variety of new methods and models of physics instruction, software, computer simulations, experiments, among others, have become available as a remedial course to the problem. In this work we present the development and application of a Potentially Meaningful Teaching Unit (PMTU), aiming to introduce Thermal Physics and Crystallography concepts in high school. Our PMTU is based on the construction of a motorized mechanical simulator designed to represent atoms from a crystal lattice of a solid material. The device was primarily designed to facilitate the abstraction on the thermal motion of a crystal lattice. Our proposal is based on David Ausubel's theory of meaningful learning, whose most important elements are the students' prior knowledge and their predisposition to learn. Our educational product consists of a didactic sequence elaborated in the form of handouts (ebook) for the teacher and for the student, tutorials for the construction of the mechanical simulator and a measuring device, named as vibrometer, and a website for the availability of the elaborated material and also to establish a centralized remote channel of communication between the teacher and the students through forums, discussions and for delivering the proposed activities. The Teacher Ebook was prepared with the answers to the proposed problems, as well as pedagogical recommendations and suggestions for developing the activities in the classroom. The Student Ebook is a simplified version of that. The ebook format is established to facilitate printing and to individualize their use. Our PMTU was applied to students of a high school class, at a private school in the city of São Roque, municipality of Sao Paulo, Brazil. Owing the COVID-19 pandemic, the application of the product was carried out almost entirely online. Our proposal was hugely successful in the classroom. The students engaged in a very satisfactory way in the development of the activities, allowing a better abstraction on the microscopic behavior of solid systems.